OP0134 Nonsteroidal antiinflammatory drugs and hospitalizations for gastrointestinal complications in china. (1st June 2001) - Chen, SL; Kong, SX; Bao, CD; Mavros, P; Chen, S; Pei, J
Abstract : Background: It has been well established that nonsteroidal antiinflammatory drugs (NSAID) cause gastrointestinal (GI) adverse events, ranging from minor symptoms to major complications leading to hospitalisation or death. Objectives: Assess the association between NSAID use and GI hospitalizations in China. Methods: The Shanghai Ren Ji Hospital is a tertiary medical centre located in central Shanghai, China. With 700 beds, the hospital has about 10, 000 admissions per year. We identified cases from the hospital medical records from 1995 to 1999 based on modes of presentation [acute abdominal pain, vomiting, hematemesis, melena, shock (pulse >100 bpm/systolic <100 mmHg), asymptomatic anaemia, other GI problems, or reason unknown with a discharge diagnosis related to GI complications]. One control was identified for each case, matched by age, sex, and admission date. Data were collected on demographics, history, diagnoses and treatment during the hospitalisation from the medical records. NSAID exposure was determined by drug use during the 1-year period prior to admission noted by the admitting physician. Logistic regression analysis was used to determine the association between NSAID use and GI complications after adjusting for age, sex, marital status, smoking history, and prior GPA use. Results: 939 patients with upper GI problems were identified as cases and of these 435 had upper GI complications as the primary diagnosis. 939 patients admitted without any GI problems were identified as controls. The mean age was 53 years and 87% were male in both groups. During the 1-year period prior to admission, cases were more likely to be NSAID users than controls (8.5% vs. 5.0%, p < 0.05). Similarly, use of gastroprotective agents (GPA, proton pump inhibitors and H2-antagonists) in the same time period was higher among cases than controls (35.9% vs. 0.6%, p < 0.05). Based on an analysis of the 939 cases and the corresponding controls, the odds ratio (OR) for GI hospitalizations of NSAID users versus nonusers adjusted by age, sex, marital status and history of smoking were 1.9 (95% CI: 1.3–2.7). Similar analysis using only the 435 cases with upper GI complications as the primary diagnosis resulted in an OR estimate of 3.1 (95% CI: 2.1–4.8). Adjusting for GPA use prior to hospital admission did not change the results. Conclusion: Among patients hospitalised in Shanghai, GI cases were significantly more likely to have used NSAIDs in the prior year than were controls. This suggests that use of NSAIDs is a significant, independent risk factor for GI hospitalisation in Shanghai, as has been demonstrated in numerous studies in developed countries.